Find the product of (2x + 5y)2. (2 points)

Answers

Answer 1
Answer: 4x + 10y

Hope it’s right
Best luck with your studying

Related Questions

James has $120 in his saving account and plans to have $x each month for 6 months. the expression $6x $120 represents the total amount in the account after 6 months. factor the expression 6x 20
The power generated by a wind turbine depends on the wind speed . The expression 800 v^3 gives the power in watts for a certain wind turbine at wind speed v in meters per second . If the wind speed triples , by what factor does the power generated by the wind turbine increase ? 2) Can you write the expression 49x^2y^2z^2 using only one exponent ? Show how or explain why not ?
Factor 9x6 – 16 y completely.First factor each term.9x6 = (__)?16y6 = ()2Then use a? - b2 = (a - b)(a + b). Show your work.9x6 – 16y6 =
What is the square root of 160/4
4(8x + 1) − 3x = 2 − 3(4x + 2)good luck!

6 children need to share 5 breakfast bars Divide bars into correct numbers of equal parts then tell the fraction each kid will get

Answers


-- Carefully cut each bar into  6  equal pieces.
   There are  (5 x 6) = 30 pieces all together.
   Each piece is  1/6  of a bar.

-- Each child gets  5  of the pieces.
   That's the same as  5/6  of a whole bar.
   (6 children) x (5 pieces) = 30 pieces.    It works out.  yay !


Solve for x.6 – 3(2x – 4) = 2(1 + x)

A. -2
B. 0
C. -1
D. 2

Answers

6 - 3(2x - 4) = 2(1 + x)   Use the Distributive Property (Multiply the number on the                                outside of the parentheses by all of the numbers in                                            parentheses to get rid of the parentheses.)
6 - 6x + 12 = 2 + 2x     Isolate the variable. Start by subtracting 2 from both                                           sides.
6 - 6x + 12 - 2 = 2x     Combine like terms. (6, 12, and -2)
16 - 6x = 2x                Add 6x to both sides to get all the x's on one side of the                                    equation.
16 = 8x                       Divide both sides by 8.
2 = x

X equals D. 2 .


Hi Brainiac

6 - 3(2x - 4) = 2(1 + x)
Use the distributive property
6+(-3)(2x)+(-3)(-4) = (2)(1)+(2)(x)
6 - 6x + 12 = 2 + 2x
Now we need to combine like terms
-6x +(6+12) = 2x +2
-6x + 18 = 2x + 2
-6x -2x = 2 - 18
-8x = -16
x = -16/-8
x= 2

I hope that's help... If you have any further questions please let me know. Good night :)

Solución por favor ayuda

Answers

The vertex is (4, -2) and the graph goes down.

One half of the sum of one and a number

Answers

(1 + x)/2    There you go

Can someone help me ? Please

Answers

Answer: if you go to calculator soup you can look up fraction calc or simplily just look up 3 and 1 half divided by 2 thirds i hope this heloed

Step-by-step explanation:

Answer:

3/7

Step-by-step explanation:

i think this is the right answer

What is the 9th term in the addition pattern with formula 7n – 3? A.13

B.42

C.60

D.76

Answers

replace n with 9 :
7 × 9 - 3 = 60
the answer is C.60